2012
DOI: 10.1111/j.1748-1716.2012.02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban and cardiac function: a comparative perspective in vertebrates

Abstract: Phospholamban (PLN) is a small phosphoprotein closely associated with the cardiac sarcoplasmic reticulum (SR). Dephosphorylated PLN tonically inhibits the SR Ca-ATPase (SERCA2a), while phosphorylation at Ser16 by PKA and Thr17 by Ca(2+) /calmodulin-dependent protein kinase (CaMKII) relieves the inhibition, and this increases SR Ca(2+) uptake. For this reason, PLN is one of the major determinants of cardiac contractility and relaxation. In this review, we attempted to highlight the functional significance of PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 149 publications
(157 reference statements)
0
21
0
Order By: Relevance
“…TAC upregulated the Akt/mTOR/S6K axis ( Figure 1B-1D) and MYH 7 ( Figure 1J), a thick filament protein that controls myofilament Ca 2+ sensitivity via PKA 14 signaling, and this effect was prevented by ALO. The level of phosphorylated phospholamban, which is regulated by PKA, 15 was decreased in TAC, and this effect was reversed by ALO ( Figure 1H). In contrast, AMPK, ERK, MYH 6, troponin T-C, troponin I, and SERCA2a were upregulated in TAC but insensitive to ALO ( Figure II in the Data Supplement; Figure 1E-1G and 1I).…”
Section: Alo Ameliorates Tac-induced Cardiac Dysfunction and Remodelingmentioning
confidence: 93%
“…TAC upregulated the Akt/mTOR/S6K axis ( Figure 1B-1D) and MYH 7 ( Figure 1J), a thick filament protein that controls myofilament Ca 2+ sensitivity via PKA 14 signaling, and this effect was prevented by ALO. The level of phosphorylated phospholamban, which is regulated by PKA, 15 was decreased in TAC, and this effect was reversed by ALO ( Figure 1H). In contrast, AMPK, ERK, MYH 6, troponin T-C, troponin I, and SERCA2a were upregulated in TAC but insensitive to ALO ( Figure II in the Data Supplement; Figure 1E-1G and 1I).…”
Section: Alo Ameliorates Tac-induced Cardiac Dysfunction and Remodelingmentioning
confidence: 93%
“…In addition to being itself a transmembrane protein of the sarcoplasmic reticulum, it is regulated by several membrane-bound proteins that include sarcolipin and phospholamban (Cerra and Imbrogno, 2012;Gorski et al, 2013). If the membrane pacemaker concept accurately predicts cypriniform biochemistry, Ca 2+ -ATPase activity should vary with body mass and/or membrane composition.…”
Section: Correcting Allometric Relationships For Phylogenymentioning
confidence: 99%
“…In addition, a large body of literature discusses the regulation of VACCs in various cell types through their phosphorylation by PKA, including chromaffin cells [55]. Conversely, the cAMP pathway significantly regulates the machinery responsible for the clearance of the [Ca 2+ ]c transients elicited by cell stimulation [56]. Most Ca 2+ clearance during cell stimulation and at the end of the stimulation period is mediated by the PMCA (plasma membrane Ca 2+ ATPase pump) and the plasmalemmal NCX (Na + /Ca 2+ exchanger) isoforms that are particularly active in cardiac myocytes, neurons and the kidney.…”
Section: Interactions Between Ca 2+ and Campmentioning
confidence: 99%
“…Most Ca 2+ clearance during cell stimulation and at the end of the stimulation period is mediated by the PMCA (plasma membrane Ca 2+ ATPase pump) and the plasmalemmal NCX (Na + /Ca 2+ exchanger) isoforms that are particularly active in cardiac myocytes, neurons and the kidney. The main exchanger isoform is NCX1 that has several splice variants [56,57]. Various studies suggested that the cardiac NCX can be phosphorylated by PKA on sites located in the large intracellular loop, which increases its activity [57].…”
Section: Interactions Between Ca 2+ and Campmentioning
confidence: 99%